Formation of heteroduplex DNA during mammalian intrachromosomal gene conversion. - Bollag, R J (1992)
We have studied intrachromosomal gene conversion in mouse Ltk- cells with a substrate designed to provide genetic evidence for heteroduplex DNA. Our recombination substrate consists of two defective chicken thymidine kinase genes arranged so as to favor the selection of gene conversion products. The gene intended to serve as the recipient in gene conversion differs from the donor sequence by virtue of a palindromic insertion that creates silent restriction site polymorphisms between the two genes. While selection for gene conversion at a XhoI linker insertion within the recipient gene results in coconversion of the nearby palindromic site in more than half of the convertants, 4% of convertant colonies show both parental and nonparental genotypes at the polymorphic site. We consider these mixed colonies to be the result of genotypic sectoring and interpret this sectoring to be a consequence of unrepaired heteroduplex DNA at the polymorphic palindromic site. DNA replication through the heteroduplex recombination intermediate generates genetically distinct daughter cells that comprise a single colony. We believe that the data provide the first compelling genetic evidence for the presence of heteroduplex DNA during chromosomal gene conversion in mammalian cells.